2019
DOI: 10.1007/s11469-019-0055-5
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Emotional Abuse and Cyberbullying Perpetration Among Adolescents: The Mediating Role of Trait Mindfulness

Abstract: Preliminary studies have indicated that childhood emotional maltreatment (i.e., abuse and neglect) can be associated with higher cyberbullying perpetration (CBP) among university students. The purpose of the present study was to test the direct and indirect effects of childhood emotional abuse (CEA) on CBP via trait mindfulness and trait emotional intelligence (TEI). A total of 470 adolescent students participated in the study and completed a questionnaire comprising measures of the aforementioned variables. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 59 publications
(66 reference statements)
2
36
0
Order By: Relevance
“…Thus, it is likely that ACEs may lead to lower PWB and poorer health outcomes by way of reduced mindfulness, a construct that is strongly related to emotional and self-regulation capacity. Indeed, studies have shown that ACEs are negatively related to mindfulness [ 55 , 56 ] and may serve as a mediator between ACEs and PWB or other related health outcomes [ 57 , 58 , 59 ]. For example, using 743 patients aged between 18 and 30, Nagel and colleagues found that ACEs were significantly and negatively associated with dispositional mindfulness ( p < 0.001), a trait that allows one to be aware of the present moment.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is likely that ACEs may lead to lower PWB and poorer health outcomes by way of reduced mindfulness, a construct that is strongly related to emotional and self-regulation capacity. Indeed, studies have shown that ACEs are negatively related to mindfulness [ 55 , 56 ] and may serve as a mediator between ACEs and PWB or other related health outcomes [ 57 , 58 , 59 ]. For example, using 743 patients aged between 18 and 30, Nagel and colleagues found that ACEs were significantly and negatively associated with dispositional mindfulness ( p < 0.001), a trait that allows one to be aware of the present moment.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…MAAS assesses dispositional mindfulness, or open and receptive awareness of and attention to what is taking place in the present moment. The results showed that mindfulness acts as a partial mediator of the association between ACEs and cyberbullying [ 58 ]. Different measures have been used to assess mindfulness, with some focusing on dispositional mindfulness (e.g., MAAS and CAMS-R), while others offering more comprehensive measures that include both mindful attention and metacognition (e.g., FFMQ) [ 55 , 56 , 57 ].…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…Second, health professionals who attempt to reduce cyberbullying perpetration should inform and warn those who perpetrate cyberbullying about the undesired effects of childhood emotional abuse on their personality and behavioral development. This information would help promote improvement of self-awareness and recognition of the underlying impulses that lead to the engagement in aggressive and antisocial online behaviors (Emirtekin et al, 2019). related to cyber aggression, childhood trauma, and behavioral addictions.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…If early childhood experiences have important effects on behavioral development (Bandura, 2001), then individuals who have been exposed to emotionally abusive behaviors as a child are at increased risk of becoming abusive individuals, the so-called cycle of violence (Wang et al, 2019). This cycle might not only manifest itself in interpersonal violence but may also manifest in the online space as a consequence of greater moral disengagement (Wang et al, 2019) and limited compassion for oneself and lack of emotional intelligence (Emirtekin et al, 2019). As such, it was expected that childhood emotional abuse would be associated with cyberbullying.…”
mentioning
confidence: 99%
“…Empirical evidence indicates that ACEs are negatively associated with mindfulness; this is true across applications of various mindfulness measurement instruments (16,18,19). Emirtekin et al (18) found that adolescents' dispositional mindfulness-defined as open and receptive awareness of and attention to the present moment and measured by the Mindful Attention Awareness Scale (MAAS)-has a significant negative correlation with childhood emotional abuse (N = 470; r = −0.46; p < 0.001). In another study by Nagel et al (19), there was a significant negative association (p < 0.001) between ACEs and dispositional mindfulness, measured by the Revised Cognitive and Affective Mindfulness Scale (CAMS-R).…”
Section: Introductionmentioning
confidence: 99%